Radically human : how new technology is transforming business and shaping our future - Daugherty, Paul R.; Wilson, H. James (Boston, Massachusetts : Harvard Business Review Press, 2022)
"Technology advances are making tech more...human. This changes everything you thought you knew about innovation and strategy. In their groundbreaking book Human + Machine, Accenture technology leaders Paul Daugherty and H. James Wilson showed how leading organizations use the power of human-machine collaboration to transform their processes and their bottom lines. Now, as AI continues to rapidly impact both life and work, those companies and other pioneers across industries are tipping the balance even more strikingly toward the human with technology-led strategy that is reshaping the very nature of innovation. In Radically Human, Daugherty and Wilson show this profound shift, fast-forwarded by the pandemic, toward more human-and more humane-technology. Artificial intelligence is becoming less artificial and more intelligent. Instead of data-hungry approaches to AI, innovators are pursuing data-efficient approaches that enable machines to learn as humans do. Instead of replacing workers with machines, they are unleashing human expertise to create human-centered AI. In place of lumbering legacy IT systems, they are building cloud-first IT architectures able to continuously adapt to a world of billions of connected devices. And they are pursuing strategies that will take their place alongside classic winning business formulas like disruptive innovation. These against-the-grain approaches to the basic building blocks of business-Intelligence, Data, Experience, Architecture, and Strategy (IDEAS)-are transforming competition. Industrial giants and startups alike are drawing on this radically human IDEAS framework to create new business models, optimize post-pandemic approaches to work and talent, rebuild trust with their stakeholders, and show the way toward a sustainable future. With compelling insights and fresh examples from a variety of industries, Radically Human will forever change the way you think about, practice, and win with innovation"--
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on June 15, 2022).
WorldCat record variable field(s) change: 050
Keywords: Artificial intelligence; Technological innovations; Business -- Data processing; Artificial Intelligence; Intelligence artificielle; Innovations; Gestion -- Informatique; artificial intelligence; Artificial intelligence; Business -- Data processing; Technological innovations; elektronické knihy; electronic books